Data science education in the iSchool context. Issue 1 (18th October 2019) - Oh, Sam; Song, Il‐Yeol; Mostafa, Javed; Zhang, Yin; Wu, Dan
ABSTRACT: The Data Science (DS) has grown in depth, breadth, and relevance in recent years as a prominent multidisciplinary field. iSchools have been among many contributing units in DS education; however, the question remains as to what unique characteristics and core curricula iSchools can best fit in and provide in the DS education landscape. This panel presents the iSchool Data Science Curriculum Committee (iDSCC)'s initiatives to address this question and report on related progress. It will also engage discussion with and seek input from the conference audience in an effort to uncover additional input on the unique characteristics of DS education in the iSchool context and core DS curriculum for iSchools.